THE SIGNIFICANCE OF LEARNING ENGLISH IN THE GLOBALIZED WORLD (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
In today’s globalized society, learning English provides valuable opportunities for communication and networking. As the primary language of international business, trade, and diplomacy, it enables individuals to connect with people from diverse cultural backgrounds. Proficiency in English enhances communication skills, expands professional connections, and grants access to a vast range of information and resources. Additionally, it makes traveling more convenient, as English is widely spoken in many countries, allowing for easier interaction with locals and navigation of new places.